Personalized Virtual Reality for Upper Extremity Rehabilitation: Moving from the Clinic to a Home Exercise Program - Behar, Cherie; Lustick, Maxwell; Foreman, Matthew H.; Webb, Jennifer; Engsberg, Jack R. (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Introduction: Traditional rehabilitation does not provide adequate repetitions for maximal motor recovery in the clinic and home exercise programs (HEPs) have low compliance rates. Personalized virtual reality (PVR) is a promising low-cost therapeutic tool for improving compliance by incorporating the client’s interests, abilities, and goals into a motivating and engaging intervention using internet games. Objectives: The current study aimed to develop and refine a clinic-to-home PVR intervention, determine its feasibility and usability in an outpatient rehabilitation clinic and as a HEP, and examine its effects on motivation/engagement, compliance, motor repetitions, and functional motor performance. Methods: The PVR system utilizes a Microsoft Kinect sensor to track the participants’ movements, free software to translate movements to keystrokes, and free internet games. The therapist matched participants’ interests to internet games, customized therapeutic movements for game play, and increased the movement thresholds for game activation as participants improved. Two participants who had strokes resulting in upper extremity (UE) hemiplegia were recruited. The participants attended outpatient occupational therapy (OT) services twice weekly. Following training, the participants used the PVR system at home in place of their UE HEP. They continued to receive traditional OT once a week and clinic-PVR once a week for 5-8 weeks. Results: The PVR intervention was successfully implemented in the clinic and the clients’ homes. PVR increased motivation and treatment compliance. The clients exhibited improvements in UE active range of motion, function, symptoms, and occupational performance. Conclusion: Preliminary evidence suggests PVR can improve motivation, compliance, function, and occupational performance. However, larger scale studies and protocol refinement are necessary.